Problems and management of technical file review reports: Case study of the Calana drinking water treatment plant in Tacna - Flores Mello, Alfonso Oswaldo (2023)
The Peruvian standard for the execution of contract works, requires that within the first month of execution, the contractor and supervisor hand in a technical file review report. However, it does not establish the procedures and/or actions that the entity, supervisor, or contractor carry out in the face of consultations, possible additions, or alerted risks, i.e., variations. In a similar situation, during the execution of the Calana potable water Treatment Plant in the city of Tacna, some additions were approved after 70 and 103 days of having identified their requirement in the technical file review reports, generating 107 days of extension of the deadline. Therefore, when reviewing possible improvements, it is proposed to modify Article 175, Requirements for the subscription of the contract work, to obtain timely communication between the contractor, supervisor, entity, and draftsman; and Article 177 on Technical file review of the work, to: i) initiate the review from the signing of the contract, with all the contractor and supervisor key personnel, ii) have direct communication with the draftsman, iii) define the structure of the report, identifying and alerting the critical date to avoid deadline extensions, and iv) start the work after answering the consultations, approving the additions, or mitigating the risks that could generate extensions. Therefore, the proposed improvements could enhance the execution of contract works.